Rethinking Group-Based Development Approach in Nepal: Ways Forward - Maskey, Stuty (New Angle: Nepal Journal of Social Science and Public Policy, 2014)
Over the last few decades, the role of ‘group-formation’ for community development has drawn substantial interest from policy makers, academics and development practitioners. This paper aims to examine the growing popularity of these development groups especially in the context where ‘groups’ are now the common entry point in most development programmes and projects in Nepal. The increasing popularity of the group approach, however, brings attention to some important questions. Is group formation a sin-qua-non for community development? Does group mobilisation always work out as per expectation? The purpose of this paper is not to provide a complete alternate option to the group approach but rather raise a note of caution on why excessive reliance on this approach must be viewed cautiously. By highlighting some issues related to this approach, this paper claims that although groups formed for community development have great potential, they should not be viewed as a panacea for developing communities; instead they should be viewed as an important component in tackling developmental challenges.